Gas exchanges and photochemical efficiency of West Indian cherry cultivated with saline water and potassium fertilization - Adaan S. Dias; Geovani S. de Lima; Francisco V. da S. Sá; Hans R. Gheyi; Lauriane A. dos A. Soares; Pedro D. Fernandes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The problem of the lack of adequate water resources for agriculture has intensified in recent years, making it necessary to use waters with relatively high concentration of salts for the irrigation of crops all over the world. The objective of this study was to evaluate the influence of potassium (K) fertilization as a salt stress attenuator on gas exchanges and photochemical efficiency of West Indian cherry. The crop was cultivated under greenhouse conditions in the municipality of Campina Grande, PB, in lysimeters filled with 250 kg of sandy loam soil. Treatments were distributed in randomized blocks, in a 2 x 4 factorial scheme, with two levels of electrical conductivity of irrigation water - ECw (0.8 and 3.8 dS m-1) and four K doses (50, 75, 100 and 125% of recommendation), in which the dose corresponding to 100% was equal to 19.8 g of K2O, with three replicates and one plant per repetition. Seedlings of the West Indian cherry cultivar BRS 366-Jaburu, grafted onto a locally developed rootstock from the clonal garden of the EMBRAPA Tropical Agroindustry, Pacajus, CE, were used. Irrigation with salinized water (electrical conductivity of 3.8 dS m-1) compromised the gas exchange and the photochemical efficiency of West Indian cherry plants. Potassium fertilization was not efficient at reducing the stress caused by water salinity on West Indian cherry plants.